PROSES PELESTARIAN TATO PADA SUKU DAYAK IBAN DI DESA BATU LINTANG KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - Junita Deputri; Fatmawati Fatmawati; Dahniar Th Musa (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze and describe the forms of tattoo preservation and the factors supporting tattoo preservation among the Dayak Iban sub-tribe in Batu Lintang Village, Embaloh Hulu District, Kapuas Hulu Regency. This is a qualitative study with a descriptive ethnographic approach using qualitative data collection techniques. The data analysis theory refers to Max Weber's views on social actions, which include: instrumental rational actions, value-rational actions, affective actions, and traditional actions. The results of the study show that the process of preserving Dayak Iban tattoos is carried out through four forms of social action: instrumental rational actions, value-rational actions, affective actions, and traditional actions. Tattoos, known locally as pantang, are an important part of the cultural identity of the Dayak Iban tribe and contain spiritual, social, and historical values that have been passed down from generation to generation. The community maintains the use of motifs typical of Dayak Iban tattoos, such as eggplant flowers, andu fruit, engkabang, and tumpa lengan, which represent a spiritual connection with nature. This preservation is supported by individual awareness, understanding of cultural values, and community support, which is manifested in traditional education, cultural festivals, and the use of social media and technology. Tattoos can be seen not only as an expression of art, but also as an intangible cultural heritage with deep meaning and value that is worth preserving and passing on